Duke and I - Quinn, Julia (New York, N.Y. Avon Books, 2000)
The rakish Duke of Hastings will stop at nothing to hold the marriage-mongers and matchmakers of his town at bay, even if it means pretending to be engaged to the lovely Daphne Bridgerton, but strong feelings soon intervene on both sides of this convenient arrangement.
"An Avon romantic treasure."
99030
Keywords: Mate selection; Marriage; Man-woman relationships; England -- Nobility -- Fiction; Historical fiction; Love stories